Prevalence Of Thyroid Disorders In Coastal Andhra Pradesh - Ravi Shekhar,; V Siva Prabodh,; NVS Chowdary,; Desai Vidya,; MC Das, (International Journal of Pharma and Bio Sciences, 2012)
Objective - To study the prevalence of thyroid dysfunction in post iodization phase and its correlation with dyslipidemia in coastal Andhra Pradesh. Materials and Method – 1330 subjects attending the NRI General Hospital for annual check up from January 2011 to December 2011 were taken into the study. Subjects included into the study were non-smoker, non-alcoholic or without any medication, not undergone thyroidectomy or exposure to radioiodine. The analysis of serum sample collected from subjects was performed on Dade Behring for lipid profile and Centaur CP for thyroid profile. The subjects were divided into 4 groups on the TSH level obtained. Results- In the thyroid disorders, prevalence of overt hypothyroidism was 31.3%, subclinical hypothyroidism was 50 %, and overt hyperthyroid was 18.7%.Discussion – Positive correlation was observed between TSH and Total Cholesterol.